The Data journalism handbook - Gray, Jonathan; Bounegru, Liliana; Chambers, Lucy (O'Reilly Media, 2012)
With The Data Journalism Handbook, you'll explore the potential, limits, and applied use of this new and fascinating field. This handbook has attracted scores of contributors since the European Journalism Centre and the Open Knowledge Foundation launched the project at MozFest 2011. Through a collection of tips and techniques form leading journalists, professors, software developers, and data analysts, you'll learn how data can be wither the source of data journalism or a tool with which the story is told--or both.